Strategies for Improving the MSME Economy through the Implementation of Technology-Based Business Management - Sulaeman, Moh. Muklis; Parwati, Anjelina Sindy; Saputra, M. Sholla Alfatih; Pinatih, Ririn; Abidin, Khoirul (Technology and Society Perspectives (TACIT), 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy. They significantly contribute to the Gross Domestic Product (GDP) and provide employment opportunities for a large portion of the workforce in the country. Despite their pivotal role, MSMEs often face various challenges such as limited access to capital, technology, and broader markets. These obstacles hinder their growth and competitiveness both nationally and globally. This research aims to identify effective strategies to enhance the economic growth of MSMEs through the implementation of technology-based business management. The method employed in this study is a literature review using a qualitative approach and descriptive analysis. Data sourced from articles indexed in Google Scholar between 2010 and 2024. The study findings indicate that enhancing the economic viability of MSMEs through technology-based business management is a crucial strategic step in navigating the increasingly competitive global market. MSMEs play a vital role in Indonesia's economy as primary contributors to job creation and inclusive economic growth.